1999
DOI: 10.1103/physrevlett.83.4381
|View full text |Cite
|
Sign up to set email alerts
|

Spinless Impurities in High-TcCuprates: Kondo-Like Behavior

Abstract: We compare the effects of in-plane non magnetic Li + and Zn 2+ impurities on the normal state of high-Tc cuprates. 89 Y NMR shows that the extra hole introduced by Li is not localized in its vicinity. The Tc depression and induced moments on near neighbour Cu sites of Zn or Li are found identical. These effects of spinless impurities establish the major influence of the spin perturbation with respect to the charge defect. The susceptibility of the induced moment measured by 7 Li NMR displays a 1/(T+Θ) behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
197
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(214 citation statements)
references
References 20 publications
14
197
1
2
Order By: Relevance
“…In contrast, spin fluctuations grow upon underdoping in all cuprates. Therefore, we propose the suppression of Kondo screening as observed in NMR [17] to be well explained within the pseudogap Fermi-Bose Kondo model with a doping-dependent host spin gap.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, spin fluctuations grow upon underdoping in all cuprates. Therefore, we propose the suppression of Kondo screening as observed in NMR [17] to be well explained within the pseudogap Fermi-Bose Kondo model with a doping-dependent host spin gap.…”
mentioning
confidence: 99%
“…with Zn replacing Cu [16,17] -here the non-magnetic Zn induces a quasi-free magnetic moment in its vicinity, which can be related to the properties of the parent Mott insulator [18]. In particular, NMR experiments indicate Kondo screening of Zn-induced moments in optimally doped YBa 2 Cu 3 O 7−δ below the superconducting T c , but show that screening is suppressed in underdoped samples [17]. So far, theoretical analysis has been restricted to either a moment interacting with bulk spin fluctuations [10] or a moment interacting with Bogoliubov quasiparticles [6,13,19].…”
mentioning
confidence: 99%
“…This is the case in so-called pseudogap systems with a power-law DOS ρ(ǫ) ∼ |ǫ| r (r > 0) which arises in one-dimensional interacting systems, in certain zero-gap semiconductors, and in systems with long-range order where the order parameter has nodes at the Fermi surface, e.g., p-and dwave superconductors (r = 2 and 1). Of special interest are high-T c cuprate superconductors, where indeed nontrivial Kondo-like behavior has been observed associated with the magnetic moments induced by non-magnetic Zn impurities [7].The pseudogap Kondo problem has attracted a lot of attention during the last decade. A number of studies [2,3] including the initial work by Withoff and Fradkin employed a slave-boson large-N technique; further progress and insight came from numerical renormalization group (NRG) calculations [4][5][6] and the local moment approach [8].…”
mentioning
confidence: 99%
“…This is the case in so-called pseudogap systems with a power-law DOS ρ(ǫ) ∼ |ǫ| r (r > 0) which arises in one-dimensional interacting systems, in certain zero-gap semiconductors, and in systems with long-range order where the order parameter has nodes at the Fermi surface, e.g., p-and dwave superconductors (r = 2 and 1). Of special interest are high-T c cuprate superconductors, where indeed nontrivial Kondo-like behavior has been observed associated with the magnetic moments induced by non-magnetic Zn impurities [7].…”
mentioning
confidence: 99%
“…The local electronic structure near non-magnetic impurities in high-T c superconductors has attracted wide attention recently. A series of NMR experiments in YBa 2 Cu 3 O 7−x (YBCO) have shown that with the substitution of nonmagnetic Zn/Li for the Cu atoms in the CuO 2 plane, an S = 1/2 staggered magnetic moment is generated on the Cu ions in the vicinity of the impurity sites [1,2,3,4,5,6,7,8]. Below the superconducting transition temperature, the moment is partially screened in optimally doped YBCO, but remains unscreened down to the lowest temperatures in the underdoped regime [3,2].…”
mentioning
confidence: 99%